The Influence Of Investment Opportunity Set (IOS) And Profitability Towards Stock Return On Property And Real Estate Firms In Indonesia Stock Exchange For The Periods 2011 To 2013 - Grace Ruth Benedicta; Herlina Lusmeida (Bandar Lampung University, 2015)
The objective of this research is to examine the influence of investment opportunity set (IOS), return on asset (ROA), return on equity (ROE) toward stock return on property and real estate firms listed in Indonesia Stock Exchange period 2011-2013. This research is classified as associative research. The used method is descriptive statistic. This research is using classical assumption test amd double linear regression run with SPSS 20.0 software. The samples are taken from property and real estate firms listed in Indonesia Stock Exchange period 2011-2013 using purposive sampling method with total of 34 samples. The independent variable in this research are Market Value to Book of Asset (MKTBASS), Market Value to Book of Equity (MKTBEQ), Earning per Share/ Price Ratio (E/P), Capital Expenditure to Book Value of Asset (CAPBVA), Return on Asset (ROA), Return on Equity (ROE). Stock Return as dependent variable. Based on this research, the result are all of the independent variables are simultaneously significantly influence on stock return. As of partially, MKTBKASS, MKTBKEQ, ROE are significantly influence on stock return, and CAPBVA, E/P, ROA are not significantly influence on stock return